2012
DOI: 10.1590/s1808-18512012000100010
|View full text |Cite
|
Sign up to set email alerts
|

Fatores prognósticos associados ao tratamento cirúrgico da mielorradiculopatia espondilótica cervical

Abstract: RESUMOObjetivo: Identificar os fatores clínicos dos indivíduos, fatores sociais, ambientais e dos exames de imagem que se correlacionam ao resultado final de melhora neurológica em pacientes submetidos ao tratamento cirúrgico da mielopatia espondilótica cervical. Métodos: A avaliação clínica foi quantificada pela escala deficitária da JOA. Analisamos 200 casos de mielorradiculopatia cervical, operados no HC-FMUSP, no período de janeiro de 1993 a janeiro de 2007. A média de segmento foi de 06 anos e 08 meses. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Meluzzi et al observed better improvement in the JOA score after surgery in the group with spinal cord compression at one level compared to the multiple-level group. 19 In the present study, the group with myelopathy at one level had a significantly higher mean postoperative JOA score (mean JOA=14.3) than the multiple-level group (mean JOA=10.6) (p=0.017). Functional and neurological recovery tended to be more favorable and have a better prognosis in the cases with single-level myelopathy.…”
Section: Discussionmentioning
confidence: 39%
See 2 more Smart Citations
“…Meluzzi et al observed better improvement in the JOA score after surgery in the group with spinal cord compression at one level compared to the multiple-level group. 19 In the present study, the group with myelopathy at one level had a significantly higher mean postoperative JOA score (mean JOA=14.3) than the multiple-level group (mean JOA=10.6) (p=0.017). Functional and neurological recovery tended to be more favorable and have a better prognosis in the cases with single-level myelopathy.…”
Section: Discussionmentioning
confidence: 39%
“…The condition of patients above 70 years of age had tended to worsen at the 24-month evaluation. 19 Myelopathy occurs due to three physiopathological factors: static, dynamic, and ischemic mechanics. Accentuated hypertrophy of the yellow ligament, instability, cervical vertebral subluxation, and low medullary vascularization (ischemia) are factors frequently encountered in the elderly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies analyzed and demonstrated the postoperative evolution taking into account the patient's age, smoking history, compromised levels, and cervical spine instability. 9…”
Section: Discussionmentioning
confidence: 99%
“…Success in the surgical treatment of the patient with spondylotic cervical myelopathy is highly dependent on the previous factors presented by the patient. Some studies analyzed and demonstrated the postoperative evolution taking into account the patient's age, smoking history, compromised levels, and cervical spine instability 9 .…”
Section: Originalmentioning
confidence: 99%